SEBARAN RUANG TERBUKA HIJAU JAGAKARSA - Rachmawati, Nia (MODUL, 2016)
Acceleration in urban development had impact to environment and urban spatial. The increase of physical development and urban infrastructure influence to decreasing quantity of green open space. The green open space needs as one of solution to bind up the relationship between human. The population increased as benchmark of green open spaces needed in the region.. The purpose of this study is: (1) identify spread of green open spaces in Jagakarsa, (2) analize the needed of green open space The analysis method based on spread and land cover constrained by sub district and district garden in Jagakarsa. The spreading of district garden Jagakarsa had not spread which is need government policy to secure and increase spreading the green open space.Â